CRISPR/Cas9-mediated targeted mutation of the E1 decreases photoperiod sensitivity, alters stem growth habits, and decreases branch number in soybean - Wan, Zhao; Liu, Yingxiang; Guo, Dandan; Fan, Rong; Liu, Yang; Xu, Kun; Zhu, Jinlong; Quan, Le; Lu, Wentian; Bai, Xi; Zhai, Hong (Frontiers in Plant Science, 2022)
Soybean (Glycine max) is highly sensitive to photoperiod, which affects flowering time and plant architecture and thus limits the distribution of elite soybean cultivars. The CRISPR/Cas9 technology has brought new opportunities for genetic manipulation in soybean. The major maturity gene E1 of soybean plays the most critical role in soybean photoperiod response. To investigate the real function of soybean E1 in photoperiod regulation, especially in architecture regulation, in this study, CRISPR/Cas9-mediated targeted mutation of E1 was conducted in soybean cultivar Tianlong1 carrying the dominant E1. Four types of mutations at the E1 coding region were generated, no off-target effects were observed, and homozygous trans-clean mutants without T-DNA were obtained. The photoperiod sensitivity of e1 mutants decreased, but e1 mutants still responded to photoperiod. The homologs of E1, E1-La and E1-Lb, are up-regulated in the e1 mutant, indicating a genetic compensation response of E1 and its homologs. The e1 mutants demonstrated great changes in the architecture, including initiated terminal flowering, thus forming determinate stems and formed decreased branch numbers. To identify E1-regulated genes in plant architecture regulation, transcriptome deep sequencing (RNA-seq) was used to compare the gene expression profiles in the stem tip of the wild-type soybean cultivar and the e1 mutant. The expression of shoot identity gene Dt1 was significantly decreased, Dt2 was significantly upregulated, and a set of MADS-box genes was up-regulated in the stem tip of e1 mutants which might contribute to the determinate stem growth habit.